The Effect of Product Innovation and Digital Promotion on Purchasing Decisions with Brand Awareness as an Intervening Variable at Fashion Businesses in Gowa Regency - Jufri, Eka Dian Hikmayani; Rakib, Muhammad; Jufri, Muhammad (Kirana Publisher (KNPub), 2025)
This study aims to analyze the effect of product innovation and digital promotion on purchasing decisions with Brand Awareness as an intervening variable at Fashion Businesses in Gowa Regency. In the context of increasingly fierce competition in the fashion industry, innovation, and digital-based marketing strategies are key to improving competitiveness. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). Data were collected through questionnaires distributed to 100 respondents who were fashion businesses customers, then analyzed using SmartPLS version 4.00 software. The results show that product innovation and digital promotion have a significant effect on Brand Awareness, with a loading factor value above 0.7 and Average Variance Extracted (AVE) meeting the validity criteria. Brand Awareness is also proven to mediate the positive influence of product innovation and digital promotion on purchasing decisions. Path analysis reveals that Brand Awareness acts as an intervening variable that strengthens the relationship between marketing strategy and purchasing decisions.